2010
DOI: 10.21608/jfds.2010.82112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Balady Bread With Rice Bran on the High Blood Glucose and Cholesterol Levels

Abstract: There is an increasing interest with rice bran due to its natural phytochemicals content such as phenolic acids and Vit E which have been reported as strong antioxidants. The purpose of this study was to produce and study the effect of supplementing Balady bread with rice bran on blood glucose and cholesterol levels in diabetic rats. Chemical composition shows that rice bran is good source of protein, minerals, dietary fiber and antioxidants such as phenolic acids and vitamin E. Balady bread was supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Cholesterol values reported in this study were similar to those reported by Bragagnolo and Rodriguez-Amaya (2003). Even though a number of human (Prasad, 2011;Lai et al, 2012;Mäkynen et al, 2012) and animal (Mobarak et al, 2010) studies have shown that RB and RB oil have hypocholesterolemic effects, results of this experiment suggest that such an effect does not exist in quail.…”
Section: Table1 Ingredient Composition and Nutrient Composition Of Tsupporting
confidence: 85%
“…Cholesterol values reported in this study were similar to those reported by Bragagnolo and Rodriguez-Amaya (2003). Even though a number of human (Prasad, 2011;Lai et al, 2012;Mäkynen et al, 2012) and animal (Mobarak et al, 2010) studies have shown that RB and RB oil have hypocholesterolemic effects, results of this experiment suggest that such an effect does not exist in quail.…”
Section: Table1 Ingredient Composition and Nutrient Composition Of Tsupporting
confidence: 85%
“…In conclusion, egg laying rate and egg quality insignificantly affected by rice bran, however, the results showed significant improvements in blood and egg yolk lipid profile and diminished oxidative status as a result of inclusion fresh rice bran in the diet. A number of human (Lai et al, 2012;Mäkynen et al, 2012) and animal (Mobarak et al, 2010) studies have shown that rice bran and rice bran oil have hypocholesterolemic effects, results of this experiment suggested that such an effect does exist in laying Japanese quail.…”
Section: Resultsmentioning
confidence: 67%
“…The influence of coriander seeds, nano-powders, and red algae on color parameters was highlighted 17 , 20 , 28 . The impact of watermelon rinds and rice bran was assessed 23 , 25 , and wheat grain fertilization techniques were compared 29 . However, olive oil amounts did not significantly change ciabatta bread color 30 .…”
Section: Introductionmentioning
confidence: 99%